Evaluation of Bermuda grass (Cynodon dactylon (L.) Pers.) and Bahia grass (Paspalum notatum Flugge) for short-term drought tolerance targeting low-maintenance landscaping - Beneragama, Chalinda Koshitha; Kapila Kumara, Ganege Don (International Journal of Applied Sciences and Biotechnology, 2018)
Drought responses of turf-type Bermuda grass (Cynodon dactylon (L.) Pers.) and Bahia grass (Paspalum notatum Flugge) in relation to their growth, carbon allocation and accumulation of nonstructural carbohydrates were investigated. Seedlings were exposed to a 20 day terminal drought, followed by 20 day recovery with irrigation. Leaf dry matter was lower in water-stressed plants than control plants by the end of drought, but did not differ in roots. For both species, more carbon was allocated towards roots in response to drought. Total nonstructural carbohydrate (TNC) concentration in shoots was increased in drought-stressed plants of both species. However, root TNC concentrations in Bahia grass were decreased after drought. TNC pool sizes also showed a similar variation, hence correlated with TNC concentrations. Bahia grass maintained a better quality than Bermuda grass after the drought, having recorded a higher aesthetic score, higher relative water content and a lower electrolyte leakage. Results suggest that, both species are considerably tolerant to short-term drought though Bahia grass seems more promising.Int. J. Appl. Sci. Biotechnol. Vol 6(1): 12-16